The Effect of Training and Motivation on Performance in the Moderation of Team Cooperation of Bank Indonesia Representative Office in North Sumatra Province - Azhari; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
This study aims to change the bad habits of organizations and can improve them to cover their shortcomings, and to determine the influence of training and motivation on performance in the moderation of the Bank Indonesia Representative Office Team in North Sumatra Province. In every company, there is a great need for a useful organization to meet the needs of humans. The goal in general in a company is to realize quality production results and maintain the survival of a company. In an effort to achieve this goal, the main driving factor is humans. Human Resources (HR) is one of the main factors for the survival of a company. The results of this study are as follows: Training has an effect on performance moderated by Teamwork obtained positive but not significant results with a sample value of 0.072 and p values of 0.229. Motivation had an effect on performance moderated by Teamwork with an original sample value of -0.140 and p values of 0.129. Teamwork had a positive and significant effect on Performance with the original sample value of 0.310 and p values of 0.006. Motivation had a positive and significant effect on Performance with the original sample value of 0.462 and p values of 0.000. The training had a positive and insignificant effect on Performance with the original sample of 0.157 and p values of 0.116.